2017
DOI: 10.1007/s12325-017-0561-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Soft Tissue Sarcoma: Proposals for the Optimal Use of Pazopanib, Trabectedin, and Eribulin

Abstract: Soft tissue sarcoma (STS) is a rare tumor with more than 50 histologic subtypes. Although treatment outcomes for patients with STS have improved greatly over the past few decades owing to the adoption of a multidisciplinary approach, patients with advanced disease have a poor prognosis. The development of anticancer drugs has been directed toward improving overall survival (OS). Doxorubicin monotherapy is currently the only standard option for the first-line treatment of STS. However, there is no standard ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 39 publications
(76 reference statements)
1
58
0
Order By: Relevance
“…Several potential molecular therapeutic targets have emerged recently for STSs. Unfortunately, the clinical trials that target them have shown little benefit for patients with refractory STSs, including synovial sarcoma and fibrosarcoma . This has led us to investigate whether GSK3β could be a useful target for the treatment of these sarcoma types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several potential molecular therapeutic targets have emerged recently for STSs. Unfortunately, the clinical trials that target them have shown little benefit for patients with refractory STSs, including synovial sarcoma and fibrosarcoma . This has led us to investigate whether GSK3β could be a useful target for the treatment of these sarcoma types.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50 histological subtypes of STS are defined by the WHO classification, with each having a different treatment response and prognosis . As a result of the wide range of histological subtypes and occurrence at various sites, STS patients are treated by different clinical departments, which ultimately complicates a general overview of STS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthracycline-based regimes are the first-line therapy [3,4]. Second-line chemotherapeutic agents for synovial sarcoma include Pazopanib, Trabectedin, and Eribulin [4][5][6][7]. For metastatic cases, chemotherapy is the main treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategy for patients with LPS includes chemotherapy, radiation therapy, surgical and tissue sparing. However, the complete treatment of LPS is a challenge 6,7 . Therefore, a new strategy is required for a more effective treatment.…”
Section: Introductionmentioning
confidence: 99%